Developmental abnormalities in cortical GABAergic system in mice lacking mGlu3 metabotropic glutamate receptors. Issue 12 (30th October 2019) - Imbriglio, Tiziana; Verhaeghe, Remy; Martinello, Katiuscia; Pascarelli, Maria Teresa; Chece, Giuseppina; Bucci, Domenico; Notartomaso, Serena; Quattromani, Miriana; Mascio, Giada; Scalabrì, Francesco; Simeone, Antonio; Maccari, Stefania; et al.
Abstract : Polymorphic variants of the gene encoding for metabotropic glutamate receptor 3 (mGlu3) are linked to schizophrenia. Because abnormalities of cortical GABAergic interneurons lie at the core of the pathophysiology of schizophrenia, we examined whether mGlu3 receptors influence the developmental trajectory of cortical GABAergic transmission in the postnatal life. mGlu3 ‐/‐ mice showed robust changes in the expression of interneuron‐related genes in the prefrontal cortex (PFC), including large reductions in the expression of parvalbumin (PV) and the GluN1 subunit of NMDA receptors. The number of cortical cells enwrapped by perineuronal nets was increased in mGlu3 ‐/‐ mice, suggesting that mGlu3 receptors shape the temporal window of plasticity of PV+ interneurons. Electrophysiological measurements of GABAA receptor‐mediated responses revealed a more depolarized reversal potential of GABA currents in the somata of PFC pyramidal neurons in mGlu3 ‐/‐ mice at postnatal d 9 associated with a reduced expression of the K + /Cl ‐ symporter. Finally, adult mGlu3 ‐/‐ mice showed lower power in electroencephalographic rhythms at 1‐45 Hz in quiet wakefulness as compared with their wild‐type counterparts. These findings suggest that mGlu3 receptors have a strong impact on the development of cortical GABAergic transmission and cortical neural synchronization mechanisms corroborating the concept that genetic variants of mGlu3 receptors may predispose to psychiatric disorders.— Imbriglio, T., Verhaeghe, R., Martinello, K., Pascarelli, M. T., Chece, G., Bucci, D., Notartomaso, S., Quattromani, M., Mascio, G., Scalabrì, F., Simeone, A., Maccari, S., Del Percio, C., Wieloch, T., Fucile, S., Babiloni, C., Battaglia, G., Limatola, C., Nicoletti, F., Cannella, M. Developmental abnormalities in cortical GABAergic system in mice lacking mGlu3 metabotropic glutamate receptors. FASEB J. 33, 14204‐14220 (2019). www.fasebj.org